PENGARUH CITRA MERK DAN KEPERCAYAAN MERK TERHADAP KEPUASAN TAMU MELALUI KEPUTUSAN MENGINAP DI HOTEL SANTIKA - Annisa Rizka Amalia; Meylani Tuti (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
The model used in this study is a quantitative method where the research is conducted by distributing questionnaires to customers who have stayed at the Santika hotel which is carried out systematically based on the research objectives. Processing of data analysis is carried out by conducting a Likert Scale Test, Validity Test, Reliability Test, SEM analysis method, structural model test (Inner Model), Measurement Model Test (Outer Model), using the PLS application version 0.3. The results of the research conducted at the Santika Hotel which is seen based on the results of the partial test stated that there is an influence between brand image, brand trust on guest satisfaction through stay decisions.